2015
DOI: 10.1111/1471-0528.13730
|View full text |Cite
|
Sign up to set email alerts
|

Clinical indication and timing of antenatal corticosteroid administration at a single centre

Abstract: Objective To determine how well antenatal corticosteroids (ACS) were timed, based on the indication for administration for women delivering preterm.Design Retrospective cohort study.Setting Tertiary medical centre.Population Six hundred and thirty women who had singleton preterm births between 24 and 34 weeks' gestational age.Methods Charts from 2006 to 2011 were reviewed for indications for ACS administration, which included premature rupture of membranes, threatened preterm labour, risk factors for spontaneo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
48
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 13 publications
8
48
1
9
Order By: Relevance
“…The timing of ACS influences the likelihood of benefit from treatment. In this study, optimal timing of ACS was achieved in 40.8% of the women, a rate comparable to others’ . The timing of ACS varied greatly depending on the obstetric indication for treatment; women with PPROM or vaginal bleeding had a median ACS delivery interval of more than seven days, significantly longer than women treated for other indications.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The timing of ACS influences the likelihood of benefit from treatment. In this study, optimal timing of ACS was achieved in 40.8% of the women, a rate comparable to others’ . The timing of ACS varied greatly depending on the obstetric indication for treatment; women with PPROM or vaginal bleeding had a median ACS delivery interval of more than seven days, significantly longer than women treated for other indications.…”
Section: Discussionsupporting
confidence: 80%
“…The ACS delivery interval varies and the proportion of optimally timed ACS (>24 h and ≤7 days before delivery) is generally poor . Previous studies have confirmed that women with PPROM have a longer ACS delivery interval compared with women with other obsteric indications .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported variable ACS administration rates among live births below 35 weeks gestation of between 35–93% . While not always clear as to whether such administration relates to a partial or complete single course of ACS as evaluated in this study, studies reporting optimal administration have uniformly demonstrated low rates of 25–50% of livebirths, More recently, interest has grown in determining what defines optimal ACS administration. While often regarded and studied as administration occurring more than 24 h but less than seven days following the first dose, there is still evidence that ACS use reduces neonatal death even when birth occurs within 24 h of the first dose .…”
Section: Discussionmentioning
confidence: 99%
“…It is positive that iatrogenic preterm birth was associated with the highest rates of optimal ACS timing, but this is still achieved in less than half of the women. Such findings are in agreement with previous studies, but raise questions as to what degree optimal administration rates can be improved. The unpredictable occurrence and varying clinical courses with regard to when delivery occurs spontaneously or is medically indicated across various obstetric complications make optimal ACS administration a challenge, with future investigations needed to better determine optimal steroid administration strategies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation